Detection and metrology of optical vortex helical wave fronts - Bogatiryova, G.V.; Soskin, M.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Spatial structure of optical vortex helical wave fronts is for the first time directly tested using various interference arrangements and precise measuring techniques. Experimental data are compared with simulation results. On this base, advantages of interference technique of any kind for testing of optical vortices in solving the specific problems are revealed.